PIOGLITAZONE MAY RECONSTITUTE THE HMGB1 PROTEIN EXPRESSION LOWERED BY HIGH GLUCOSE CONDITION IN INSULINOMA CELLS - Khoo Boon-Yin,; Aysegül Depboylu,; Brigitte Lankat-Buttgereit ,; Rüdiger Göke , (Tropical Life Sciences Research, 2007)
Pioglitazone is a Peroxisome proliferator-activated receptor-gamma (PPAR?) agonist that has been widely used as an insulin-sensitizing drug to reduce insulin resistance in type II diabetic patients. Previous studies demonstrated that the high mobility group box-1 (HMGB1) protein level of insulinoma cell line (INS-1) cells was reduced by high glucose treatment. The study, therefore, determined that pioglitazone is able to reconstitute the expression of HMGB1 protein in a high glucose condition. For this purpose, INS-1 cells were incubated in medium without serum, supplemented with either 10 mM or 30 mM glucose, with or without an addition of 40 ?M of pioglitazone. The HMGB1 protein expression from each treated cells was then examined by Western blot. The results demonstrated that pioglitazone may be potentially useful to reconstitute the HMGB1 protein expression in high glucose condition, which may provide important information on the mechanism of action of pioglitazone in diabetes treatment.